Revisiting the moisture budget of the Mediterranean region in the ERA5 reanalysis - R. Tootoonchi; S. Bordoni; R. D'Agostino (Weather and Climate Dynamics)
Moisture budget assessments from reanalyses and climate models have provided fundamental insights into the maintenance and response to perturbations of the hydrological cycle in the Mediterranean region. Here we perform similar analyses using the latest-generation European Centre for Medium-Range Weather Forecasts (ECMWF) re-analysis (ERA5), and we complement previous work by further decomposing the mean flow into contributions by the zonal-mean flow, which is dominated by the mean meridional circulation, and by zonally anomalous circulations and/or moisture, namely stationary eddies. According to ERA5, in the annual mean, net evaporation (negative P–E) over the ocean and net precipitation (positive P–E) over land are primarily due to submonthly transient eddies converging moisture originating from the ocean into the surrounding land. Overall, total stationary eddies reinforce the transient tendency over the ocean but oppose it over land, with the zonal-mean flow exerting a minor drying tendency limited to the region's southernmost latitudes. The total stationary eddy moisture flux divergence arises from a strongly divergent zonally anomalous circulation acting on the zonal-mean moisture. This is partly opposed by the pure stationary eddy term, which provides moisture flux convergence through both divergence and advection of zonally anomalous moisture by the zonally anomalous circulation. The relative magnitude of these terms changes over the seasonal cycle, explaining the transition from net precipitation during winter (DJF) to net evaporation during summer (JJA) over land. More specifically, as transient eddies weaken during the warm season, the strengthened divergent total stationary eddy moisture flux becomes dominant and causes strong drying and negative net precipitation. Somewhat surprisingly, moisture flux divergence by the mean meridional circulation is found to play a minor role in the Mediterranean region across all seasons except autumn (SON).